Status of seed-borne fungi in some indigenous medicinal and aromatic plants conserved in National Gene Bank, India - PARDEEP KUMAR, ASHOK KUMAR MAURYA, DINESH CHAND, VEENA GUPTA; SUNIL CHANDRA DUBEY, JAMEEL AKHTAR*, BALESHWAR SINGH, A.KANDAN (Indian Phytopathology, 2017)
During 2011-2015, seed health testing (SHT) of 880 accessions representing more than 60 crop species of medicinal and aromatic plants (MAPs) germplasm resulted in detection and identification of 17 fungal species belonging to 11 genera. Based on morphological key characteristics, various pathogens, namely Botrytis cinerea, Cephalosporium maydis, Colletotrichum gloeosporioides, Fusarium equiseti, F. oxysporum, F. semitectum, F. solani, F. verticillioides, Lasiodiplodia theobromae, Macrophomina phaseolina, Melanospora zamiae, Myrothecium roridum, M. verrucaria, Phoma exigua var. exigua, P. sorghina, Ustilago coicis and Verticillium albo-atrum were recorded on 71 accessions (8.1%) of MAPs germplasm with varying level of seed infections (10-50%). Pathogen wise overall infection showed the highest infection share of U. coicis (44.4%) followed by P. sorghina (19.4%) and B. cinerea (11.1%) among 71 infected accessions. A perusal of literature indicated that detection of B. cinerea and M. roridum on Vernonia anthelmintica; C. maydis and M. verrucaria on Costus speciosus; C. gloeosporioides and M. phaseolina on Abroma augusta; F. equisetiÂ on Origanum vulgare; F. verticillioides on C. speciosus, Mucuna pruriens and T. cucumerina; L. theobromae on C. speciosus, T.cucumerina and T. bracteata; P. exigua var. exigua on T.cucumerina; and P. sorghina on Coix lacryma-jobi, C. speciosus, Ochna lanceolata, Perilla frutescens, Tagetus patula, T. cucumerina and T. bracteata are new host records on MAPs germplasm from India. If such infected seeds are conserved and/or distributed for either research purpose or their commercial use, they may act as a source of inocula dissemination and hamper the cultivation of MAPs leading to losses in quality and yield. Therefore, detection of seed infection through seed health testing is important in conserving disease-free material so as to minimize the risk of spreading disease in the country.